1998
DOI: 10.3109/13506129809007285
|View full text |Cite
|
Sign up to set email alerts
|

Laminin blocks the assembly of wild-type Aβ and the Dutch variant peptide into Alzheimer's fibrils

Abstract: Amyloid fibril formation is believed to be a nucleation-dependent polymerization process which may be influenced by various other factors with important consequences for the development, prevention or treatment of amyloidosis. We have previously shown that laminin inhibits A beta peptide fibril formation in vitro. Here we present a kinetic study that indicates laminin to be a potent anti-amyloidosis factor, as it not only inhibited A beta 1-40 fibril aggregation, but also inhibited the aggregation of the Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Laminin, nidogens, and collagen IV are vascular basement membrane proteins that inhibit aggregation of Ab and destabilize preformed fibrils of Ab (Bronfman et al, 1998). Vessels under 50 lm in diameter from AD patients show a decrease in the amount of collagen IV, compared with aged-matched controls (Christov et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminin, nidogens, and collagen IV are vascular basement membrane proteins that inhibit aggregation of Ab and destabilize preformed fibrils of Ab (Bronfman et al, 1998). Vessels under 50 lm in diameter from AD patients show a decrease in the amount of collagen IV, compared with aged-matched controls (Christov et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that biochemical and morphological alterations to basement membranes contribute to the development of CAA. In vitro incubation of Ab with laminin, collagen IV, and nidogen has been shown to prevent Ab fibrillization, whereas agrin and perlecan promote and stabilize Ab fiber formation (Castillo et al, 1997;Bronfman et al, 1998;Cotman et al, 2000;Kiuchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to AChE, we have also found that the extracellular matrix protein laminin, which is located peripherally to amyloid deposits in experimental rat models, inhibits the process of A fibril formation [31,32] and even may disaggregate amyloid fibrils in vitro [5]. In the Fig.…”
Section: Lamininmentioning
confidence: 92%
“…Its expression seems to be increased after brain injury (26) and in the brain of AD and Down syndrome patients (27). In order to examine the pathological significance of laminin induction in Alzheimer brains, we studied the effect of laminin on Aß peptide polymerization, and we showed for the first time that laminin was a (28,29). Figure 1A shows a turbidity assay indicating that Aß aggregation in the presence of laminin was clearly decreased, and that the formation of amyloid was also diminished in the presence of laminin, as evidenced by Congo red staining ( Figure 1B).…”
Section: The Anti-amyloidogenic Role Of Lamininmentioning
confidence: 99%